Acrylic adhesive sheet, acrylic adhesive composition, adhesive film, and flexible device

The acrylic adhesive sheet and composition address flexibility and adhesion issues in conventional films by combining high adhesive strength with low elasticity, ensuring durability in flexible devices through a polymerization process.

JP7629034B2Active Publication Date: 2025-02-12NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022578119
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-26
Filing Date
2021-12-10
Publication Date
2025-02-12
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

Conventional adhesive films used in semiconductor devices and flexible devices suffer from poor flexibility and adhesion when bent, leading to issues like wrinkles, deformation, and detachment due to inadequate elasticity and adhesive strength, especially when the adhesive layer thickness is reduced.

Method used

An acrylic adhesive sheet and composition are developed with specific monomer components and a reduced thickness, achieving both excellent adhesive properties and elasticity, with a storage modulus of 200 kPa or less and adhesive strength of 5.5N/25mm or more, using a polymerization process to form an adhesive layer.

Benefits of technology

The acrylic adhesive sheet maintains strong adhesion and flexibility, even with a thin layer, preventing deformation and detachment in repeated bending, suitable for flexible devices like folderable and roller devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629034000010
    Figure 0007629034000010
  • Figure 0007629034000001
    Figure 0007629034000001
  • Figure 0007629034000002
    Figure 0007629034000002
Patent Text Reader

Abstract

Provided are: an acrylic pressure-sensitive adhesive sheet which, even when the pressure-sensitive adhesive layer has a reduced thickness, can have both excellent tackiness and excellent elasticity; an acrylic pressure-sensitive adhesive composition which forms the acrylic pressure-sensitive adhesive sheet; a pressure-sensitive adhesive film including a pressure-sensitive adhesive layer constituted from the acrylic pressure-sensitive adhesive sheet; and a flexible device including the pressure-sensitive adhesive film. The acrylic pressure-sensitive adhesive sheet according to an embodiment of the present invention has an adhesive force in application to a polyimide film of 5.5 N / 25 mm or greater and an adhesive force in application to a glass of 5.5 N / 25 mm or greater, both as measured at 23°C, a peeling rate of 300 mm / min, and a peeling angle of 180°, and has a storage modulus G' at -20°C of 200 kPa or less and a thickness of 25 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an acrylic pressure-sensitive adhesive sheet, an acrylic pressure-sensitive adhesive composition, an adhesive film, and a flexible device. [Background technology]

[0002] Adhesive films are used for reinforcing members of various shapes and for protecting the surfaces.

[0003] For example, when joining an integrated circuit (IC) or a flexible printed circuit (FPC) to a substrate of a semiconductor element (e.g., a TFT substrate, etc.), thermocompression bonding is usually performed using an anisotropic conductive film (ACF). When performing such thermocompression bonding, an adhesive film may be attached to the back side of the substrate of the semiconductor element in advance to reinforce the substrate (e.g., Patent Document 1).

[0004] In addition, in a manufacturing method for so-called flexible devices such as foldable devices and rollable devices, which have been developed in recent years, a release layer and a flexible film substrate are generally formed on a support substrate such as glass, a TFT substrate is formed on the film substrate, and an organic EL layer is further formed on the TFT substrate. The support substrate is then peeled off to manufacture a flexible device, but since the flexible display layer is very thin, problems with the device occur due to handling, etc. For this reason, an adhesive film may be attached to the back side to reinforce it (for example, Patent Document 2).

[0005] Substrates of semiconductor elements and flexible devices may be repeatedly bent, and if the bending properties of the adhesive film attached to the substrate, etc. are poor, the recovery after bending may be poor, or in the worst case, the film may break due to repeated bending. Specifically, when an adhesive film is attached to a bending portion (e.g., a movable bending portion of a folding member), for example, the following problems may occur.

[0006] When an adhesive film is bent at an angle, a compressive force acts on the bent inner diameter side, and the adhesive film itself deforms in an attempt to relieve this force. Specifically, for example, the film becomes more prone to wrinkles.

[0007] When an adhesive film is bent at an angle, a tensile stress acts on the outer diameter side of the bent part, and when the stress is relieved, the film floats off the adherend.

[0008] When an adhesive film is bent at an angle, the thickness of the bent or pulled part of the adhesive film changes significantly, and even in this state, the adhesive film is prone to wrinkles and lifting. For example, when an adhesive film is pulled, the thickness of the adhesive film becomes significantly thinner, making it more likely to lift off from the adherend.

[0009] Thus, conventional adhesive films are unable to adequately conform to uneven corners and bent portions.

[0010] One approach to solving the above problems is to improve the elasticity by reducing the thickness of the adhesive layer, but reducing the thickness of the adhesive layer makes it difficult to maintain the adhesive strength. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Patent No. 5600039 [Patent Document 2] Patent No. 6376271 Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide an acrylic pressure-sensitive adhesive sheet which is capable of achieving both excellent adhesion and excellent elasticity even when the thickness of the pressure-sensitive adhesive layer is thin; an acrylic pressure-sensitive adhesive composition which forms the acrylic pressure-sensitive adhesive sheet; an adhesive film having an adhesive layer constituted by the acrylic pressure-sensitive adhesive sheet; and a flexible device which includes the adhesive film. [Means for solving the problem]

[0013] The acrylic pressure-sensitive adhesive sheet according to an embodiment of the present invention comprises: At 23°C, at a peel speed of 300 mm / min and a peel angle of 180°, the adhesive strength to polyimide film is 5.5 N / 25 mm or more, and the adhesive strength to glass is 5.5 N / 25 mm or more. The storage modulus G' at -20°C is 200 kPa or less, The thickness is 25 μm or less.

[0014] The acrylic pressure-sensitive adhesive composition according to an embodiment of the present invention comprises: An acrylic pressure-sensitive adhesive composition for forming an acrylic pressure-sensitive adhesive sheet according to an embodiment of the present invention, Contains acrylic polymer (P) and oligomer.

[0015] In one embodiment, the acrylic polymer (P) is obtained by polymerizing a monomer component (M), and the monomer component (M) contains a monomer (m5) having a polar group other than a hydroxyl group.

[0016] In one embodiment, the content of the monomer (m5) having a polar group other than a hydroxyl group in the monomer component (M) is 0.1% by weight to 5.0% by weight.

[0017] In one embodiment, the monomer (m5) having a polar group other than a hydroxyl group includes at least one selected from the group consisting of a monomer (1) represented by general formula (1), a monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone. [ka] (In general formula (1), R 1 is an alkyl group having 1 to 10 carbon atoms, and R 2 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a -COOR group, and R is an alkyl group having 1 to 10 carbon atoms. [ka] (In general formula (2), R 3 is an alkylene group having 1 to 10 carbon atoms, R 4 is an alkyl group having 1 to 10 carbon atoms, and R 5 is a hydrogen atom or a methyl group.

[0018] In one embodiment, the content of the oligomer in the acrylic pressure-sensitive adhesive composition is 0.1 to 6.5 parts by weight based on 100 parts by weight of the acrylic polymer (P).

[0019] In one embodiment, the oligomer has a weight average molecular weight Mw of 1,000 to 30,000.

[0020] In one embodiment, the monomer component (M) comprises an alkyl (meth)acrylate.

[0021] In one embodiment, the glass transition temperature Tg of the homopolymer of the alkyl (meth)acrylate is −10° C. or lower.

[0022] In one embodiment, the content of the alkyl (meth)acrylate in the monomer component (M) is 50% by weight to 99% by weight.

[0023] In one embodiment, the monomer component (M) includes a hydroxyl group-containing monomer (m4).

[0024] In one embodiment, the content of the hydroxyl group-containing monomer (m4) in the monomer component (M) is 0.01% by weight to 30% by weight.

[0025] The pressure-sensitive adhesive film according to the embodiment of the present invention has a pressure-sensitive adhesive layer constituted by the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention.

[0026] A flexible device according to an embodiment of the present invention includes an adhesive film according to an embodiment of the present invention. Effect of the Invention

[0027] Effects of the Invention According to the present invention, it is possible to provide an acrylic pressure-sensitive adhesive sheet which is capable of achieving both excellent adhesion and excellent elasticity even when the thickness of the pressure-sensitive adhesive layer is reduced, an acrylic pressure-sensitive adhesive composition which forms the acrylic pressure-sensitive adhesive sheet, an adhesive film having an adhesive layer constituted by the acrylic pressure-sensitive adhesive sheet, and a flexible device which includes the adhesive film. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a flexible device of the present invention, and shows one mode of use of an adhesive film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein". In this specification, the term "acid (salt)" means "acid and / or its salt". Examples of salts include alkali metal salts and alkaline earth metal salts, and specific examples include sodium salts and potassium salts.

[0030] <<Acrylic adhesive sheet>> The acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention is a sheet-shaped acrylic pressure-sensitive adhesive, and therefore may be an acrylic pressure-sensitive adhesive sheet that can be handled independently, or may be recognized as one of the components, such as an acrylic pressure-sensitive adhesive layer.

[0031] The acrylic adhesive sheet according to the embodiment of the present invention has an adhesive strength to a polyimide film at 23°C, a peel speed of 300 mm / min, and a peel angle of 180 degrees of preferably 5.5 N / 25 mm or more, more preferably 6.0 N / 25 mm or more, even more preferably 6.5 N / 25 mm or more, even more preferably 7.0 N / 25 mm or more, particularly preferably 7.5 N / 25 mm or more, and most preferably 8.0 N / 25 mm or more. The upper limit of the adhesive strength is usually the higher the better, but taking into account the balance with other adhesive properties, it is preferably 30 N / 25 mm or less. If the adhesive strength is adjusted within the above range, sufficient adhesiveness to various adherends such as flexible devices such as foldable devices and rollable devices can be exhibited. The measurement of the adhesive strength will be described later.

[0032] The acrylic adhesive sheet according to the embodiment of the present invention has an adhesive strength to a glass plate at 23°C, a peeling speed of 300 mm / min, and a peeling angle of 180 degrees of preferably 5.5 N / 25 mm or more, more preferably 6.0 N / 25 mm or more, even more preferably 6.5 N / 25 mm or more, even more preferably 7.0 N / 25 mm or more, particularly preferably 7.5 N / 25 mm or more, and most preferably 8.0 N / 25 mm or more. The upper limit of the adhesive strength is usually the higher the better, but taking into consideration the balance with other adhesive properties, it is preferably 30 N / 25 mm or less. If the adhesive strength is adjusted within the above range, sufficient adhesiveness to various adherends such as flexible devices such as foldable devices and rollable devices can be exhibited. The measurement of the adhesive strength will be described later.

[0033] The acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention typically has an adhesive strength to polyimide film within the above range, and an adhesive strength to glass within the above range, at a peel speed of 300 mm / min and a peel angle of 180° at 23° C. The fact that the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention has such adhesive properties means that the adhesive properties of the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention are low dependent on the adherend.

[0034] The acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention has a storage modulus G' at -20°C of preferably 200 kPa or less, more preferably 180 kPa or less, even more preferably 160 kPa or less, even more preferably 150 kPa or less, even more preferably 140 kPa or less, particularly preferably 130 kPa or less, and most preferably 120 kPa or less. The lower limit of the storage modulus G' is preferably 70 kPa or more, taking into consideration the balance with other pressure-sensitive adhesive properties. If the storage modulus G' is adjusted within the above range, the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention can exhibit excellent elasticity. If the storage modulus G' is too large outside the above range, the elasticity may decrease. The measurement of the storage modulus G' will be described later.

[0035] The thickness of the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention is preferably 25 μm or less, more preferably 23 μm or less, even more preferably 20 μm or less, even more preferably 18 μm or less, particularly preferably 15 μm or less, and most preferably 13 μm or less. The thinner the thickness, the better, but considering the balance with other pressure-sensitive adhesive properties, the lower limit of the thickness is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 9 μm or more. If the thickness of the acrylic pressure-sensitive adhesive sheet is within the above range, the thin thickness of the acrylic pressure-sensitive adhesive sheet can be realized.

[0036] It is more preferable that the adhesive strength to the polyimide film, the storage modulus G' at -20°C, and the thickness of the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention are all adjusted within the above ranges. By adjusting in this way, the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention can achieve both excellent adhesiveness and excellent elasticity even if the thickness of the pressure-sensitive adhesive layer is reduced.

[0037] The acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention is preferably formed from an acrylic pressure-sensitive adhesive composition.

[0038] The acrylic pressure-sensitive adhesive sheet can be defined as one formed from an acrylic pressure-sensitive adhesive composition in this way. This is because the acrylic pressure-sensitive adhesive sheet becomes an acrylic pressure-sensitive adhesive sheet when the acrylic pressure-sensitive adhesive composition undergoes a crosslinking reaction or the like due to heating or exposure to ultraviolet light, and therefore it is impossible and practical to directly define the acrylic pressure-sensitive adhesive sheet by its structure ("impossible / impractical circumstances") exist, and therefore the acrylic pressure-sensitive adhesive sheet is appropriately defined as a "product" by the definition of "one formed from an acrylic pressure-sensitive adhesive composition."

[0039] When the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention is formed from an acrylic pressure-sensitive adhesive composition, any suitable method may be adopted as a method for forming such an acrylic pressure-sensitive adhesive sheet within a range that does not impair the effects of the present invention. For example, a method for forming such an acrylic pressure-sensitive adhesive sheet includes applying an acrylic pressure-sensitive adhesive composition onto any suitable substrate, heating and drying as necessary, and curing as necessary to form an acrylic pressure-sensitive adhesive sheet on the substrate. Any suitable means may be adopted as a means for such application within a range that does not impair the effects of the present invention. Examples of such means for application include a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roll brush coater. Any suitable means may be adopted for heating and drying the acrylic pressure-sensitive adhesive composition within a range that does not impair the effects of the present invention. Examples of such means for heating and drying include heating to about 60°C to 180°C. The acrylic pressure-sensitive adhesive composition may be cured by any suitable means as long as the effects of the present invention are not impaired. Examples of such curing means include ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.

[0040] <<Acrylic pressure-sensitive adhesive composition>> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention is an acrylic pressure-sensitive adhesive composition for forming an acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention.

[0041] <Acrylic polymer (P)> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention preferably contains an acrylic polymer (P). The acrylic polymer (P) may be one type or two or more types. When the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains the acrylic polymer (P), the effects of the present invention can be more effectively exhibited.

[0042] The weight average molecular weight Mw of the acrylic polymer (P) may be any appropriate weight average molecular weight Mw within a range that does not impair the effects of the present invention. Such a weight average molecular weight Mw is preferably 500,000 to 2.5 million, more preferably 800,000 to 2.3 million, even more preferably 1,000,000 to 2.2 million, particularly preferably 1.1 million to 2.1 million, and most preferably 1.3 million to 1.6 million.

[0043] The content of the acrylic polymer (P) in the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention is preferably 50% by weight or more, more preferably 70% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 97% by weight or more. The upper limit of the content is preferably 99.9% by weight or less. By adjusting the content within the above range, it is possible to provide an acrylic pressure-sensitive adhesive sheet that can achieve both excellent adhesion and excellent elasticity even if the thickness of the pressure-sensitive adhesive layer is thin.

[0044] The acrylic polymer (P) is preferably obtained by polymerizing the monomer component (M).

[0045] The acrylic polymer (P) can be defined as something obtained by polymerizing the monomer component (M) in this way. This is because the acrylic polymer (P) becomes the acrylic polymer (P) through the polymerization reaction of the monomer component (M), and it is impossible to directly identify the acrylic polymer (P) by its structure, and there are circumstances that make it almost impractical ("impossible / impractical circumstances"). Therefore, the acrylic polymer (P) is appropriately defined as a "product" by the definition of "something obtained by polymerizing the monomer component (M)."

[0046] The monomer component (M) preferably contains a monomer (m5) having a polar group other than a hydroxyl group. The monomer (m5) having a polar group other than a hydroxyl group may be of only one type or of two or more types.

[0047] The content of the monomer (m5) having a polar group other than a hydroxyl group in the monomer component (M) is preferably 0.01 wt % to 40 wt %, more preferably 0.05 wt % to 20 wt %, even more preferably 0.1 wt % to 10 wt %, still more preferably 0.3 wt % to 5.0 wt %, particularly preferably 0.4 wt % to 4.0 wt %, and most preferably 0.5 wt % to 3.5 wt %, in order to further exert the effects of the present invention.

[0048] As the monomer (m5) having a polar group other than a hydroxyl group, any suitable monomer having a polar group other than a hydroxyl group may be adopted within a range that does not impair the effects of the present invention. As such a monomer (m5) having a polar group other than a hydroxyl group, a monomer having a polar group other than a hydroxyl group whose homopolymer has a glass transition temperature Tg of 100° C. or less is preferably used. The Tg is preferably 95° C. or less, more preferably 90° C. or less. The lower limit of the Tg is preferably −30° C. or more, more preferably −10° C. or more. The glass transition temperature Tg of the homopolymer of the monomer (m5) having a polar group other than a hydroxyl group may affect the adhesive properties and bending properties of the acrylic polymer (P). By adopting a monomer having a polar group other than a hydroxyl group whose homopolymer has a glass transition temperature Tg within the above range as the monomer (m5) having a polar group other than a hydroxyl group, the adhesiveness and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be more effectively expressed.

[0049] The monomer (m5) having a polar group other than a hydroxyl group, from the viewpoint of further exerting the effects of the present invention, preferably essentially contains a monomer having a polar group other than a hydroxyl group, the glass transition temperature Tg of which homopolymer is 50° C. to 100° C. The glass transition temperature Tg of the homopolymer of this monomer is preferably 60° C. to 95° C., and more preferably 70° C. to 90° C.

[0050] The content of the monomer having a polar group other than a hydroxyl group in the monomer (m5) having a polar group other than a hydroxyl group, the glass transition temperature Tg of whose homopolymer is 50°C to 100°C (preferably 60°C to 95°C, and more preferably 70°C to 90°C), is preferably 30% by weight to 100% by weight, more preferably 50% by weight to 100% by weight, even more preferably 70% by weight to 100% by weight, particularly preferably 90% by weight to 100% by weight, and most preferably 95% by weight to 100% by weight, in order to further exert the effects of the present invention.

[0051] Here, as the glass transition temperature Tg of a homopolymer of a monomer (m5) having a polar group other than a hydroxyl group that may be contained in the monomer component (M), a value described in a publicly known document can be used, for example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. In addition, when multiple values ​​are described in the "Polymer Handbook", the conventional value is used. For a monomer (m5) having a polar group other than a hydroxyl group that is not described in the "Polymer Handbook", the catalog value of the monomer manufacturer is used. As the Tg of a homopolymer of an alkyl (meth)acrylate that is not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.

[0052] The monomer (m5) having a polar group other than a hydroxyl group preferably includes at least one selected from the group consisting of a monomer (1) represented by general formula (1), a monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone. [ka] (In general formula (1), R 1 is an alkyl group having 1 to 10 carbon atoms, and R 2is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a -COOR group, and R is an alkyl group having 1 to 10 carbon atoms. [ka] (In general formula (2), R 3 is an alkylene group having 1 to 10 carbon atoms, R 4 is an alkyl group having 1 to 10 carbon atoms, and R 5 is a hydrogen atom or a methyl group.

[0053] The monomer (1) represented by the general formula (1) may be of one type only, or of two or more types.

[0054] Monomer (1) represented by general formula (1) has two polymerizable double bonds at its terminals and a structure (C-CH2-O-CH2-C) that can form a furan ring structure by cyclopolymerization. In addition, at least one of the carbon atoms second from the end of the two polymerizable double bonds at the terminals has an alkyl ester group (COOR 1 By providing the alkyl ester group, it is possible to promote cyclopolymerization and to introduce an alkyl ester group into the structure constructed by cyclopolymerization. Due to these characteristics, the obtained acrylic pressure-sensitive adhesive can exhibit both superior flexibility and superior recovery properties with respect to bending motion.

[0055] The monomer (2) represented by the general formula (2) may be of one type only, or of two or more types.

[0056] The monomer (2) represented by the general formula (2) has a (meth)acrylic acid ester structure (CH2=C(R 5 )COO-) and a carbamoyloxy structure (-O-CO-NH-), and these characteristics enable the resulting acrylic pressure-sensitive adhesive to exhibit both excellent flexibility and excellent recovery when bent.

[0057] In the monomer (1) represented by the general formula (1), R 1is an alkyl group having 1 to 10 carbon atoms, and R 1 is preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, even more preferably an alkyl group having 1 to 3 carbon atoms, particularly preferably a methyl group or an ethyl group, and most preferably a methyl group.

[0058] In the monomer (1) represented by the general formula (1), R 2 R is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a -COOR group. 2 is an alkyl group having 1 to 10 carbon atoms, the effects of the present invention can be more effectively exhibited. 2 R is preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 3 carbon atoms. 2 When R is a -COOR group, R is an alkyl group having 1 to 10 carbon atoms, and from the viewpoint of more effectively exerting the effects of the present invention, R is preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, even more preferably an alkyl group having 1 to 3 carbon atoms, particularly preferably a methyl group or an ethyl group, and most preferably a methyl group. 2 is preferably a hydrogen atom.

[0059] In the monomer (2) represented by the general formula (2), R 3 is an alkylene group having 1 to 10 carbon atoms, and R 3 is preferably an alkylene group having 1 to 8 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, even more preferably an alkylene group having 1 to 3 carbon atoms, particularly preferably a methylene group (-CH2-) or an ethylene group (-CH2CH2-), and most preferably an ethylene group (-CH2CH2-).

[0060] In the monomer (2) represented by the general formula (2), R 4 is an alkyl group having 1 to 10 carbon atoms, and R4 is preferably an alkyl group having 2 to 8 carbon atoms, more preferably an alkyl group having 3 to 6 carbon atoms, even more preferably an alkyl group having 3 to 5 carbon atoms, particularly preferably a butyl group, and most preferably an n-butyl group.

[0061] In the monomer (2) represented by the general formula (2), R 5 is a hydrogen atom or a methyl group, and R 5 is preferably a hydrogen atom.

[0062] The content of at least one selected from the group consisting of monomer (1) represented by general formula (1), monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone in the monomer component (M) is preferably 0.01% by weight to 30% by weight, more preferably 0.05% by weight to 10% by weight, even more preferably 0.1% by weight to 5.0% by weight, still more preferably 0.3% by weight to 4.0% by weight, particularly preferably 0.4% by weight to 3.5% by weight, and most preferably 0.5% by weight to 3.0% by weight, in order to further exert the effects of the present invention.

[0063] When the monomer component (M) contains the monomer (1) represented by general formula (1), the content of the monomer (1) represented by general formula (1) in the monomer component (M) is preferably 0.01% by weight to 20% by weight, more preferably 0.1% by weight to 10% by weight, even more preferably 0.2% by weight to 5.0% by weight, still more preferably 0.3% by weight to 3.0% by weight, particularly preferably 0.4% by weight to 2.0% by weight, and most preferably 0.5% by weight to 1.5% by weight, in order to further exert the effects of the present invention.

[0064] When the monomer component (M) contains the monomer (2) represented by the general formula (2), the content of the monomer (2) represented by the general formula (2) in the monomer component (M) is preferably 0.01% by weight to 20% by weight, more preferably 0.05% by weight to 10% by weight, even more preferably 0.1% by weight to 8.0% by weight, still more preferably 1.0% by weight to 6.0% by weight, particularly preferably 1.2% by weight to 4.0% by weight, and most preferably 1.5% by weight to 3.0% by weight, in order to further exert the effects of the present invention.

[0065] When the monomer component (M) contains N-vinyl-2-pyrrolidone, the content of N-vinyl-2-pyrrolidone in the monomer component (M) is preferably 0.01 wt % to 20 wt %, more preferably 0.05 wt % to 10 wt %, even more preferably 0.1 wt % to 5.0 wt %, still more preferably 0.2 wt % to 3.0 wt %, particularly preferably 0.3 wt % to 2.0 wt %, and most preferably 0.4 wt % to 1.5 wt %, in order to further exert the effects of the present invention.

[0066] Examples of the monomer (m5) having a polar group other than a hydroxyl group include, in addition to the monomer (1) represented by general formula (1), the monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone, for example, a carboxy group-containing monomer, a nitrogen-containing monomer other than N-vinyl-2-pyrrolidone, a sulfonic acid group-containing monomer, a phosphoric acid group-containing monomer, a cyano group-containing monomer, an acid anhydride group-containing monomer, vinyl esters (for example, vinyl acetate (VAc), vinyl propionate, vinyl laurate), aromatic vinyl compounds, an amide group-containing monomer, an epoxy group-containing monomer, (meth)acryloylmorpholine, and vinyl ethers.

[0067] Examples of carboxy group-containing monomers include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0068] Examples of nitrogen-containing monomers other than N-vinyl-2-pyrrolidone include nitrogen-containing vinyl monomers such as methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam; and cyano group-containing acrylic monomers such as acrylonitrile and methacrylonitrile.

[0069] The monomer component (M) preferably contains an alkyl (meth)acrylate. The alkyl group of the ester moiety is preferably an alkyl group having a carbon number of 1 to 16. The alkyl group of the ester moiety here does not include an alkyl group containing a polar group such as a hydroxyl group.

[0070] The alkyl (meth)acrylate may be used alone or in combination of two or more kinds.

[0071] The content of alkyl (meth)acrylate in the monomer component (M) is preferably 50% by weight to 99% by weight, more preferably 70% by weight to 98% by weight, even more preferably 80% by weight to 97% by weight, particularly preferably 85% by weight to 96% by weight, and most preferably 90% by weight to 96% by weight, in order to further exert the effects of the present invention.

[0072] As the alkyl (meth)acrylate, any suitable alkyl (meth)acrylate can be used as long as it does not impair the effects of the present invention. As such an alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used. CH2=C(R 1 )COOR 2 (1)

[0073] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group, and R 2 is an alkyl group having 1 to 20 carbon atoms.

[0074] R 2 is preferably an alkyl group having 1 to 16 carbon atoms, more preferably an alkyl group having 2 to 14 carbon atoms, still more preferably an alkyl group having 4 to 14 carbon atoms, and particularly preferably an alkyl group having 4 to 12 carbon atoms, in that the effects of the present invention can be more effectively exhibited.

[0075] The alkyl group is preferably a chain alkyl group, in that the effects of the present invention can be more effectively exhibited. Here, the term "chain" includes both linear and branched alkyl groups.

[0076] R 2 Examples of alkyl(meth)acrylates in which is a chain alkyl group having 1 to 20 carbon atoms include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, isooctyl(meth)acrylate, ) acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.

[0077] In terms of being able to further exert the effects of the present invention, the alkyl (meth)acrylate that can be contained in the monomer component (M) has a glass transition temperature Tg of its homopolymer (homopolymer) of preferably -10 ° C or less, more preferably -12 ° C or less, even more preferably -15 ° C or less, particularly preferably -18 ° C or less, and most preferably -20 ° C or less. The lower limit of the glass transition temperature Tg is preferably -80 ° C or more. The glass transition temperature Tg of the homopolymer (homopolymer) of the alkyl (meth)acrylate that can be contained in the monomer component (M) can affect the adhesion properties and bending properties of the acrylic polymer (P). By adopting an alkyl (meth)acrylate whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range as the alkyl (meth)acrylate that can be contained in the monomer component (M), the adhesion and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be further exerted.

[0078] Here, as the glass transition temperature Tg of the homopolymer of alkyl (meth)acrylate that may be contained in the monomer component (M), a value described in a publicly known document can be adopted, as in the case of the monomer (m5) having a polar group other than a hydroxyl group described above. For example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. If multiple values ​​are described in the "Polymer Handbook", the conventional value is adopted. For alkyl (meth)acrylates not described in the "Polymer Handbook", the catalog value of the monomer manufacturer is adopted. For the Tg of the homopolymer of alkyl (meth)acrylate that is not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.

[0079] Representative examples of the glass transition temperature Tg of a homopolymer of an alkyl (meth)acrylate that can be contained in the monomer component (M) are as follows. 2-Ethylhexyl acrylate (2EHA): -70℃ Lauryl acrylate (LA): -23℃ n-Butyl acrylate (BA): -55℃

[0080] From the viewpoint of further exerting the effects of the present invention, the monomer component (M) preferably contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m1) whose homopolymer has a glass transition temperature Tg in the range of −80° C. to −60° C. When the monomer component (M) contains the alkyl (meth)acrylate (m1), from the viewpoint of further exerting the effects of the present invention, the content of the alkyl (meth)acrylate (m1) in the monomer component (M) is preferably 40% by weight to 99% by weight, more preferably 45% by weight to 90% by weight, even more preferably 50% by weight to 80% by weight, particularly preferably 55% by weight to 75% by weight, and most preferably 60% by weight to 70% by weight.

[0081] The glass transition temperature Tg of the homopolymer of the alkyl(meth)acrylate that may be contained in the monomer component (M) may affect the adhesive properties and bending properties of the acrylic polymer (P) as described above. By adjusting the content of the alkyl(meth)acrylate (m1) in the monomer component (M) as the alkyl(meth)acrylate that may be contained in the monomer component (M) so that it falls within the above range, the adhesiveness and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be more effectively exhibited.

[0082] An example of the alkyl (meth)acrylate (m1) is 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg of its homopolymer is −70° C.).

[0083] In order to further exert the effects of the present invention, the monomer component (M) preferably contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m2) whose homopolymer has a glass transition temperature Tg in the range of −40° C. to −10° C. When the monomer component (M) contains the alkyl (meth)acrylate (m2), in order to further exert the effects of the present invention, the content of the alkyl (meth)acrylate (m2) in the monomer component (M) is preferably 5% by weight to 50% by weight, more preferably 7% by weight to 40% by weight, even more preferably 10% by weight to 30% by weight, particularly preferably 13% by weight to 25% by weight, and most preferably 15% by weight to 22% by weight.

[0084] The glass transition temperature Tg of the homopolymer of the alkyl(meth)acrylate that may be contained in the monomer component (M) may affect the adhesion and elasticity of the acrylic polymer (P) as described above. By adjusting the content of the alkyl(meth)acrylate (m2) in the monomer component (M) as the alkyl(meth)acrylate that may be contained in the monomer component (M) so that it falls within the above range, the adhesion and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be more effectively exhibited.

[0085] An example of the alkyl (meth)acrylate (m2) is lauryl acrylate (LA) (having a glass transition temperature Tg of its homopolymer of -23°C).

[0086] From the viewpoint of further exerting the effects of the present invention, the monomer component (M) preferably contains, as the alkyl (meth)acrylate, an alkyl (meth)acrylate (m3) whose homopolymer has a glass transition temperature Tg in the range of more than −60° C. and less than −40° C. When the monomer component (M) contains the alkyl (meth)acrylate (m3), from the viewpoint of further exerting the effects of the present invention, the content of the alkyl (meth)acrylate (m3) in the monomer component (M) is preferably 0.1% by weight to 30% by weight, more preferably 1% by weight to 20% by weight, even more preferably 3% by weight to 15% by weight, particularly preferably 4% by weight to 13% by weight, and most preferably 5% by weight to 10% by weight.

[0087] The glass transition temperature Tg of the homopolymer of the alkyl(meth)acrylate that may be contained in the monomer component (M) may affect the adhesion and elasticity of the acrylic polymer (P) as described above. By adjusting the content of the alkyl(meth)acrylate (m3) in the monomer component (M) as the alkyl(meth)acrylate that may be contained in the monomer component (M) so that it falls within the above range, the adhesion and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be more effectively exhibited.

[0088] An example of the alkyl (meth)acrylate (m3) is n-butyl acrylate (BA) (having a glass transition temperature Tg of its homopolymer of -55°C).

[0089] In terms of being able to further exert the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3), and even more preferably contains any of alkyl (meth)acrylates (m1), alkyl (meth)acrylates (m2), and alkyl (meth)acrylates (m3).

[0090] In terms of being able to further exert the effects of the present invention, typically, monomer component (M) preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and even more preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate.

[0091] The monomer component (M) preferably contains a hydroxyl group-containing monomer (m4). The hydroxyl group-containing monomer (m4) may be of one type only, or of two or more types.

[0092] In terms of being able to further exert the effects of the present invention, the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) has a glass transition temperature Tg of its homopolymer (homopolymer) of preferably -10 ° C. or less, more preferably -15 ° C. or less, even more preferably -20 ° C. or less, particularly preferably -25 ° C. or less, and most preferably -30 ° C. or less. The lower limit of the glass transition temperature Tg is preferably -80 ° C. or more. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) can affect the adhesion and elasticity of the acrylic polymer (P). By adopting a hydroxyl group-containing monomer (m4) whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range as the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M), the adhesion and elasticity of the acrylic polymer (P) can be appropriately adjusted, and the effects of the present invention can be further exerted.

[0093] Here, as the glass transition temperature Tg of the homopolymer of the hydroxyl-containing monomer (m4) that may be contained in the monomer component (M), values ​​described in publicly known documents can be used, as with the monomer (m5) having a polar group other than a hydroxyl group and alkyl (meth)acrylate described above. For example, values ​​described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) can be used. In addition, when multiple values ​​are described in the "Polymer Handbook", conventional values ​​are used. For hydroxyl-containing monomers (m4) that are not described in the "Polymer Handbook" and for which no catalog value is provided by a monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used as the Tg of the homopolymer of the hydroxyl-containing monomer (m4) that is not described in the "Polymer Handbook" and for which no catalog value is provided by a monomer manufacturer.

[0094] Representative examples of the glass transition temperature Tg of the homopolymer of the hydroxyl group-containing monomer (m4) that can be contained in the monomer component (M) are as follows. 2-Hydroxyethyl acrylate: -15℃ 4-Hydroxybutyl acrylate: -40℃

[0095] When the monomer component (M) contains a hydroxyl group-containing monomer (m4), in order to further exert the effects of the present invention, the content of the hydroxyl group-containing monomer (m4) in the monomer component (M) is preferably 0.01% by weight to 30% by weight, more preferably 0.1% by weight to 20% by weight, even more preferably 0.5% by weight to 15% by weight, particularly preferably 1% by weight to 10% by weight, and most preferably 2% by weight to 5% by weight.

[0096] Examples of the hydroxyl group-containing monomer (m4) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide.

[0097] In terms of being able to further exert the effects of the present invention, the hydroxyl group-containing monomer (m4) preferably contains a hydroxyalkyl (meth)acrylate, and more preferably contains a hydroxyalkyl (meth)acrylate in which the alkyl group moiety is a linear alkyl group having 2 to 4 carbon atoms. Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA), and in terms of being able to further exert the effects of the present invention, 4-hydroxybutyl acrylate is preferred.

[0098] In order to further exert the effects of the present invention, the monomer component (M) preferably contains at least one selected from the group consisting of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4), more preferably contains at least two selected from the group consisting of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4), and even more preferably contains all of alkyl (meth)acrylate (m1), alkyl (meth)acrylate (m2), and alkyl (meth)acrylate (m3), and a hydroxyl group-containing monomer (m4).

[0099] In terms of being able to further exert the effects of the present invention, typically, the monomer component (M) preferably contains at least one selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4), more preferably contains at least two selected from the group consisting of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4), and even more preferably contains all of 2-ethylhexyl acrylate, lauryl acrylate, and n-butyl acrylate, and a hydroxyl group-containing monomer (m4).

[0100] In order to further exert the effects of the present invention, the total content of the alkyl (meth)acrylate (m1), the alkyl (meth)acrylate (m2), the alkyl (meth)acrylate (m3) and the hydroxyl group-containing monomer (m4) in the monomer component (M) is preferably 60% by weight to 99.9% by weight, more preferably 70% by weight to 99.8% by weight, even more preferably 80% by weight to 99.7% by weight, particularly preferably 90% by weight to 99.6% by weight, and most preferably 95% by weight to 99.5% by weight.

[0101] The monomer component (M) may contain other monomers other than the monomer (m5) having a polar group other than a hydroxyl group, the alkyl (meth)acrylate, and the hydroxyl group-containing monomer (m4) as long as the effect of the present invention is not impaired. The other monomers can be used for the purpose of adjusting the glass transition temperature (Tg) of the acrylic polymer (P), adjusting the adhesive performance, etc. The other monomers may be one type only, or two or more types.

[0102] The content of other monomers in the monomer component (M) is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less.

[0103] As a method for obtaining the acrylic polymer (P), various polymerization methods known as a synthesis method for acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization, can be appropriately adopted. Among these polymerization methods, solution polymerization can be preferably used. As a monomer supply method when carrying out solution polymerization, a lump-sum charging method in which the entire amount of the monomer components is supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, and the like can be appropriately adopted. The polymerization temperature can be appropriately selected according to the type of monomer and solvent used, the type of polymerization initiator, and the like, and is preferably 20°C or higher, more preferably 30°C or higher, even more preferably 40°C or higher, preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 140°C or lower. As a method for obtaining an acrylic polymer, photopolymerization (typically carried out in the presence of a photopolymerization initiator) carried out by irradiating light such as UV rays, or radiation polymerization carried out by irradiating radiation such as β rays or γ rays may be adopted.

[0104] The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from any suitable organic solvent, for example, aromatic compounds (typically aromatic hydrocarbons) such as toluene, acetate esters such as ethyl acetate, aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane, etc.

[0105] The initiator (polymerization initiator) used in the polymerization can be appropriately selected from any suitable polymerization initiator depending on the type of polymerization method. The polymerization initiator may be one type only, or two or more types may be used.

[0106] Examples of the polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, and the like. hydrochloride, azo initiators such as 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl)peroxydicarbonate, di(4 peroxide-based initiators such as di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; redox-based initiators combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate; substituted ethane-based initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds.

[0107] The amount of the polymerization initiator used is preferably 0.005 to 1 part by weight, and more preferably 0.01 to 1 part by weight, based on 100 parts by weight of the monomer component (M).

[0108] The polymerization may contain any suitable other additives as long as they do not impair the effects of the present invention.

[0109] <Oligomer> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention preferably contains an oligomer. The oligomer may be of only one type or of two or more types. When the acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention contains an oligomer, the effects of the present invention can be more effectively exhibited.

[0110] The weight average molecular weight Mw of the oligomer is preferably from 1,000 to 30,000, more preferably from 1,500 to 10,000, further preferably from 2,000 to 8,000, and particularly preferably from 2,000 to 5,000. By using an oligomer having such a weight average molecular weight Mw, the adhesiveness and elasticity of the acrylic pressure-sensitive adhesive sheet can be improved.

[0111] As the oligomer, an acrylic oligomer is preferred because it is compatible with an acrylic polymer.

[0112] The glass transition temperature Tg of the acrylic oligomer is preferably 20° C. or higher, more preferably 40° C. or higher, even more preferably 60° C. or higher, particularly preferably 80° C. or higher, and most preferably 100° C. or higher. The upper limit of the glass transition temperature Tg of the acrylic oligomer is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 160° C. or lower.

[0113] The glass transition temperature Tg of an acrylic oligomer is a value calculated from the Fox formula based on the Tg of the homopolymer of each constituent monomer and the weight fraction (copolymerization ratio by weight) of the monomer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi)

[0114] In the above Fox formula, Tg is the glass transition temperature (unit: K) of the copolymer, Wi is the weight fraction (copolymerization ratio by weight) of monomer i in the copolymer, and Tgi is the glass transition temperature (unit: K) of the homopolymer of monomer i. As the Tg of the homopolymer, a value described in a publicly known document can be adopted, for example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. When multiple values ​​are described in the "Polymer Handbook", the conventional value is adopted. For monomers not described in the "Polymer Handbook", the catalog value of the monomer manufacturer is adopted. As the Tg of the homopolymer of a monomer not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.

[0115] The acrylic oligomer contains an alicyclic alkyl (meth)acrylate as a main constituent monomer component. The alicyclic alkyl (meth)acrylate may be of one type only or of two or more types.

[0116] Examples of alicyclic alkyl (meth)acrylates include cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylic acid esters having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.

[0117] As the alicyclic alkyl (meth)acrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred, in that they can further exert the effects of the present invention.

[0118] The content ratio of the alicyclic alkyl (meth)acrylate relative to the total amount of the constituent monomer components of the acrylic oligomer is preferably 10% by weight to 99% by weight, more preferably 30% by weight to 98% by weight, even more preferably 40% by weight to 97% by weight, and particularly preferably 50% by weight to 96% by weight, in order to further exhibit the effects of the present invention.

[0119] The acrylic oligomer may contain a chain alkyl (meth)acrylate having a chain alkyl group as a constituent monomer component, and the chain alkyl (meth)acrylate having a chain alkyl group may be one type or two or more types. Here, the chain alkyl group includes linear and branched.

[0120] The chain alkyl (meth)acrylate is preferably a chain alkyl (meth)acrylate having a chain alkyl group having 1 to 20 carbon atoms, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and the like. acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.

[0121] As the chain alkyl (meth)acrylate, methyl methacrylate is preferred in that the effects of the present invention can be more effectively exhibited.

[0122] The content ratio of the chain alkyl (meth)acrylate to the total amount of the constituent monomer components of the acrylic oligomer is preferably 10% by weight to 90% by weight, more preferably 20% by weight to 80% by weight, and even more preferably 30% by weight to 70% by weight, in order to further exhibit the effects of the present invention.

[0123] The acrylic oligomer may contain (meth)acrylic acid as a constituent monomer component. The (meth)acrylic acid may be of only one type, or of two or more types.

[0124] As the (meth)acrylic acid, acrylic acid is preferred in that the effects of the present invention can be more effectively exhibited.

[0125] The content of (meth)acrylic acid relative to the total amount of constituent monomer components of the acrylic oligomer is preferably 0.1 to 20% by weight, more preferably 1 to 10% by weight, and even more preferably 3 to 7% by weight, in order to further exhibit the effects of the present invention.

[0126] The oligomer can be obtained by polymerizing the constituent monomer components by various polymerization methods. When polymerizing the oligomer, any appropriate additive may be used within a range that does not impair the effects of the present invention. Examples of such additives include a polymerization initiator and a chain transfer agent.

[0127] The content of the oligomer in the acrylic pressure-sensitive adhesive composition is preferably 0.1 to 6.5 parts by weight, more preferably 0.5 to 5.5 parts by weight, even more preferably 1.0 to 4.5 parts by weight, even more preferably 1.0 to 4.0 parts by weight, still more preferably 1.0 to 3.5 parts by weight, particularly preferably 1.0 to 3.0 parts by weight, and most preferably 1.5 to 2.5 parts by weight, relative to 100 parts by weight of the acrylic polymer (P), in order to further exert the effects of the present invention.

[0128] <Crosslinking agent> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention may contain a crosslinking agent. The crosslinking agent may be of only one type, or of two or more types.

[0129] The use of a crosslinking agent can impart an appropriate cohesive strength to the acrylic pressure-sensitive adhesive. The crosslinking agent may be contained in the acrylic pressure-sensitive adhesive in a form after crosslinking reaction, a form before crosslinking reaction, a form after partial crosslinking reaction, an intermediate or composite form thereof, or the like. The crosslinking agent is typically contained in the acrylic pressure-sensitive adhesive in a form after crosslinking reaction.

[0130] The content of the crosslinking agent in the acrylic pressure-sensitive adhesive composition is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 7 parts by weight, even more preferably 0.01 to 5 parts by weight, still more preferably 0.01 to 1 part by weight, still more preferably 0.01 to 0.5 parts by weight, particularly preferably 0.01 to 0.35 parts by weight, and most preferably 0.01 to 0.1 parts by weight, relative to 100 parts by weight of the acrylic polymer (P), in order to further exert the effects of the present invention.

[0131] Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, a silicone-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a silane-based crosslinking agent, an alkyl etherified melamine-based crosslinking agent, a metal chelate-based crosslinking agent, a peroxide, and the like. In terms of being able to further exert the effects of the present invention, an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, or a peroxide is preferable, and an isocyanate-based crosslinking agent or a peroxide is more preferable.

[0132] The isocyanate crosslinking agent may be a compound having two or more isocyanate groups (including isocyanate regenerating polar groups in which the isocyanate group is temporarily protected by a blocking agent or oligomerization) in one molecule. Examples of the isocyanate crosslinking agent include aromatic isocyanates such as tolylene diisocyanate and xylylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.

[0133] Examples of the isocyanate-based crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate; trimethylolpropane / tolylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate HL), and isocyanurate of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, isocyanate adducts such as CORONATE HX; trimethylolpropane adduct of xylylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D110N), trimethylolpropane adduct of xylylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D120N), trimethylolpropane adduct of isophorone diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D140N), trimethylolpropane adduct of hexamethylene diisocyanate (e.g., Mitsui Chemicals, Inc., trade name: TAKENATE D160N); polyether polyisocyanate, polyester polyisocyanate, and adducts of these with various polyols; and polyisocyanates multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among these, aromatic isocyanates and alicyclic isocyanates are preferred because they can achieve a good balance between deformability and cohesive strength.

[0134] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, and the like. Examples of epoxy crosslinking agents include glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of commercially available epoxy crosslinking agents include "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Company, Inc.

[0135] Examples of peroxides include dibenzoyl peroxide, dicumyl peroxide, di-t-butyl peroxide, di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butyl hydroperoxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-mono(t-butylperoxy)-hexane, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy Examples of peroxides include neodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, t-butylperoxy-2-ethylhexyl carbonate, t-amyl peroxyisopropyl carbonate, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-hexanoate, t-butyl peroxypivalate, and t-hexyl peroxypivalate. Examples of commercially available peroxides include the "Nyper BMT" series manufactured by Nippon Oil & Fats Corporation.

[0136] <Tackifying resin> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention may contain a tackifier resin in order to adjust adhesive properties and bending properties, etc. The tackifier resin may be of only one type, or of two or more types.

[0137] Examples of tackifying resins include rosin-based tackifying resins, terpene-based tackifying resins, hydrocarbon-based tackifying resins, epoxy-based tackifying resins, polyamide-based tackifying resins, elastomer-based tackifying resins, phenol-based tackifying resins, and ketone-based tackifying resins.

[0138] The amount of the tackifier resin used is preferably 5 to 70 parts by weight, more preferably 10 to 60 parts by weight, even more preferably 15 to 50 parts by weight, still more preferably 20 to 45 parts by weight, particularly preferably 25 to 40 parts by weight, and most preferably 25 to 35 parts by weight, relative to 100 parts by weight of the acrylic polymer (P), in order to further exert the effects of the present invention.

[0139] The tackifier resin preferably contains a tackifier resin TL having a softening point of less than 105°C, in order to more effectively exert the effects of the present invention. The tackifier resin TL can effectively contribute to improving the deformability in the planar direction (shear direction) of the pressure-sensitive adhesive layer. From the viewpoint of obtaining a higher effect of improving deformability, the softening point of the tackifier resin used as the tackifier resin TL is preferably 50°C to 103°C, more preferably 60°C to 100°C, even more preferably 65°C to 95°C, particularly preferably 70°C to 90°C, and most preferably 75°C to 85°C.

[0140] The softening point of a tackifier resin is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at the lowest possible temperature, and is carefully filled into a ring placed on a flat metal plate, taking care not to create bubbles. After cooling, the part that protrudes from the flat surface, including the top end of the ring, is cut off with a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerin is poured in until it is 90 mm or more deep. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin without touching each other, and the temperature of the glycerin is kept at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring, and this is placed in a fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer and align the center of the thermometer's mercury bulb to the same height as the center of the ring, then heat the container. The flame of the Bunsen burner used for heating should be midway between the center of the bottom of the container and its edge, and heating should be uniform. After heating begins and the temperature of the bath reaches 40°C, the rate of increase must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate, and this is the softening point. The softening point is measured for two or more samples at the same time, and the average value is used.

[0141] The amount of the tackifier resin TL used is preferably 5 to 50 parts by weight, more preferably 10 to 45 parts by weight, even more preferably 15 to 40 parts by weight, particularly preferably 20 to 35 parts by weight, and most preferably 25 to 32 parts by weight, relative to 100 parts by weight of the acrylic polymer (P), in order to further exert the effects of the present invention.

[0142] As the tackifier resin TL, one or more types may be used that are appropriately selected from the tackifier resins exemplified above that have a softening point of less than 105° C. The tackifier resin TL preferably contains a rosin-based resin.

[0143] Examples of rosin-based resins that can be preferably used as the tackifier resin TL include rosin esters such as unmodified rosin ester and modified rosin ester. Examples of modified rosin esters include hydrogenated rosin ester.

[0144] The tackifier resin TL preferably contains a hydrogenated rosin ester, which can further exert the effects of the present invention. The softening point of the hydrogenated rosin ester is preferably less than 105°C, more preferably 50°C to 100°C, even more preferably 60°C to 90°C, particularly preferably 70°C to 85°C, and most preferably 75°C to 85°C, which can further exert the effects of the present invention.

[0145] The tackifier resin TL may contain a non-hydrogenated rosin ester. The term "non-hydrogenated rosin ester" as used herein is a general term referring to the above-mentioned rosin esters other than the hydrogenated rosin ester. Examples of the non-hydrogenated rosin ester include unmodified rosin ester, disproportionated rosin ester, and polymerized rosin ester.

[0146] The softening point of the non-hydrogenated rosin ester is preferably less than 105°C, more preferably from 50°C to 100°C, even more preferably from 60°C to 90°C, particularly preferably from 70°C to 85°C, and most preferably from 75°C to 85°C, in order to better exhibit the effects of the present invention.

[0147] The tackifier resin TL may contain other tackifier resins in addition to the rosin resin. As the other tackifier resins, one or more types appropriately selected from the tackifier resins exemplified above having a softening point of less than 105° C. may be used. The tackifier resin TL may contain, for example, a rosin resin and a terpene resin.

[0148] The content of the rosin-based resin in the entire tackifier resin TL is preferably more than 50% by weight, more preferably 55% by weight to 100% by weight, even more preferably 60% by weight to 99% by weight, particularly preferably 65% ​​by weight to 97% by weight, and most preferably 75% by weight to 97% by weight, in order to further exert the effects of the present invention.

[0149] The tackifier resin may contain a combination of a tackifier resin TL and a tackifier resin TH having a softening point of 105° C. or higher (preferably 105° C. to 170° C.), in order to further exert the effects of the present invention.

[0150] As the tackifier resin TH, one or more types appropriately selected from the above-listed tackifier resins having a softening point of 105° C. or higher can be used. The tackifier resin TH can include at least one type selected from rosin-based tackifier resins (e.g., rosin esters) and terpene-based tackifier resins (e.g., terpene phenol resins).

[0151] <Other ingredients> The acrylic pressure-sensitive adhesive composition according to the embodiment of the present invention may contain, as necessary, various additives commonly used in the field of pressure-sensitive adhesives, such as a leveling agent, a crosslinking assistant, a plasticizer, a softener, a filler, an antistatic agent, an antiaging agent, an ultraviolet absorber, an antioxidant, a light stabilizer, a crosslinking catalyst, a crosslinking retarder, etc. As for such various additives, conventionally known ones can be used in a conventional manner.

[0152] Examples of the crosslinking catalyst include ferric naphthem, tetra-n-butyl titanate, tetraisopropyl titanate, butyltin oxide, dioctyltin dilaurate, etc. Examples of the crosslinking retarder include compounds that generate keto-enol tautomerism, specifically, for example, β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetate esters such as methyl acetoacetate and ethyl acetoacetate; propionyl acetate esters such as ethyl propionyl acetate; isobutyryl acetate esters such as ethyl isobutyryl acetate; malonate esters such as methyl malonate and ethyl malonate; and the like.

[0153] <<Adhesive film>> The pressure-sensitive adhesive film according to the embodiment of the present invention has a pressure-sensitive adhesive layer constituted by the acrylic pressure-sensitive adhesive sheet according to the embodiment of the present invention.

[0154] The pressure-sensitive adhesive film according to the embodiment of the present invention may be a substrate-less film consisting of only a pressure-sensitive adhesive layer, or may be a substrate-attached film having a substrate layer and a pressure-sensitive adhesive layer. The pressure-sensitive adhesive film of the present invention may have any other appropriate layer in addition to the substrate layer and the pressure-sensitive adhesive layer, as long as the effect of the present invention is not impaired.

[0155] The substrate layer may be one layer or two or more layers, and is preferably one layer in that the effects of the present invention can be more effectively exhibited.

[0156] The pressure-sensitive adhesive layer may be one layer or two or more layers, and is preferably one layer in that the effect of the present invention can be more effectively exhibited.

[0157] The pressure-sensitive adhesive film according to the embodiment of the present invention may be provided with any appropriate release liner on the surface of the pressure-sensitive adhesive layer opposite the base layer for protection until use, etc.

[0158] Examples of the release liner include a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is silicone-treated, a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin resin, etc. Examples of the plastic film as the liner substrate include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polybutylene terephthalate film, a polyurethane film, an ethylene-vinyl acetate copolymer film, etc.

[0159] The thickness of the release liner is preferably from 1 μm to 500 μm, more preferably from 3 μm to 450 μm, even more preferably from 5 μm to 400 μm, and particularly preferably from 10 μm to 300 μm.

[0160] The thickness of the pressure-sensitive adhesive film according to the embodiment of the present invention is preferably 1 μm to 500 μm, more preferably 5 μm to 200 μm, even more preferably 10 μm to 150 μm, particularly preferably 20 μm to 100 μm, and most preferably 30 μm to 80 μm. When the thickness of the pressure-sensitive adhesive film according to the embodiment of the present invention is within the above range, the effects of the present invention can be more effectively exhibited.

[0161] The pressure-sensitive adhesive film according to the embodiment of the present invention has a total light transmittance of preferably 20% or more, more preferably 30% or more, even more preferably 40% or more, particularly preferably 50% or more, and most preferably 60% or more. If the total light transmittance of the pressure-sensitive adhesive film of the present invention is within the above range, excellent transparency can be more easily exhibited.

[0162] The adhesive film according to the embodiment of the present invention has a haze of preferably 15% or less, more preferably 13% or less, even more preferably 10% or less, particularly preferably 8% or less, and most preferably 6% or less. When the haze of the adhesive film of the present invention is within the above range, excellent transparency can be more easily exhibited.

[0163] The adhesive film according to the embodiment of the present invention can achieve both excellent adhesiveness and excellent elasticity, and therefore can be preferably used in flexible devices such as foldable devices and rollable devices.

[0164] ≪Base material layer≫ The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, further preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. When the thickness of the substrate layer is within the above range, the effects of the present invention can be more effectively exhibited.

[0165] The base layer preferably has a Young's modulus at 23° C. of 6.0×10 7 Pa or more, more preferably 1.0×10 8 Pa or more, and more preferably 5.0×10 8 Pa or more, and particularly preferably 8.0×10 8 Pa or more, and most preferably 1.0×10 9 The upper limit of the Young's modulus of the base layer at 23° C. is typically preferably 1.0×10 11 Pa or less. If the Young's modulus of the base layer at 23°C is within the above range, the effect of the present invention can be more effectively achieved. If the Young's modulus of the base layer at 23°C is too low, when the adhesive film is bent at an angle, the tension on the outer diameter side may not be sufficiently maintained against the compression on the inner diameter side, and the thickness may easily change, and the adhesive film may easily float from the adherend. If the Young's modulus of the base layer at 23°C is too high, the adhesive film may not be easily deformed. The method for measuring the Young's modulus will be described in detail later.

[0166] As the material for the base layer, any appropriate material may be used as long as it does not impair the effects of the present invention. A representative example of the material for the base layer is a resin material.

[0167] Examples of resin materials for the base layer include acrylic resins such as polyimide (PI), polyether ether ketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, and cyclic olefin polymers.

[0168] <Adhesive layer> The thickness of the adhesive layer may be that of the acrylic adhesive sheet according to the embodiment of the present invention. Therefore, the thickness of the adhesive layer is preferably 25 μm or less, more preferably 23 μm or less, even more preferably 20 μm or less, even more preferably 18 μm or less, particularly preferably 15 μm or less, and most preferably 13 μm or less. The thinner the thickness, the better, but considering the balance with other adhesive properties, the lower limit of the thickness is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 9 μm or more.

[0169] The pressure-sensitive adhesive layer is one form of an acrylic pressure-sensitive adhesive sheet. Any suitable method for forming the pressure-sensitive adhesive layer may be adopted as long as it does not impair the effects of the present invention. Examples of such a method include a method of applying an acrylic pressure-sensitive adhesive composition onto any suitable substrate, heating and drying as necessary, and curing as necessary to form an acrylic pressure-sensitive adhesive layer on the substrate. Any suitable means for such application may be adopted as long as it does not impair the effects of the present invention. Examples of such application means include a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roll brush coater. Any suitable means for heating and drying the acrylic pressure-sensitive adhesive composition may be adopted as long as it does not impair the effects of the present invention. Examples of such heating and drying means include heating to about 60°C to 180°C. Any suitable means for curing the acrylic pressure-sensitive adhesive composition may be adopted as long as it does not impair the effects of the present invention. Examples of such curing means include ultraviolet irradiation, laser irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.

[0170] Flexible Devices The adhesive film of the present invention has both excellent adhesion and excellent elasticity, and therefore can be suitably provided on flexible devices such as bendable devices (devices that can be bent) having movable bending parts, foldable devices (devices that can be folded), and rollable devices (devices that can be rolled up).

[0171] That is, the flexible device according to the embodiment of the present invention includes an adhesive film according to the embodiment of the present invention. The flexible device according to the embodiment of the present invention includes an adhesive film according to the embodiment of the present invention. The foldable device according to the embodiment of the present invention may include any other appropriate member as long as it includes an adhesive film according to the embodiment of the present invention.

[0172] FIG. 1 is a schematic cross-sectional view showing one embodiment of a flexible device of the present invention as a representative example of one use form of the adhesive film according to the embodiment of the present invention. In FIG. 1, a foldable device 1000 according to an embodiment of the present invention includes a cover film 10, an adhesive layer 20, a polarizing plate 30, an adhesive layer 40, a touch sensor 50, an adhesive layer 60, an OLED 70, and an adhesive film 100 according to an embodiment of the present invention. In FIG. 1, the adhesive film 100 according to the embodiment of the present invention is composed of an adhesive layer 80 and a base layer 90. The adhesive layer 20, the adhesive layer 40, and the adhesive layer 60 may be adhesive layers containing an adhesive of the same composition as the adhesive layer 80 constituting the adhesive film 100 according to the embodiment of the present invention, or may be adhesive layers containing an adhesive of a different composition. EXAMPLES

[0173] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited thereto. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0174] The abbreviations and details of raw materials used in the following Production Examples, Examples, and Comparative Examples are as follows: 2EHA: 2-ethylhexyl acrylate (glass transition temperature of its homopolymer Tg = -70°C) LA: Lauryl acrylate (glass transition temperature of its homopolymer Tg = -23°C) BA: n-butyl acrylate (glass transition temperature of its homopolymer Tg = -55°C) 4HBA: 4-hydroxybutyl acrylate (glass transition temperature of its homopolymer Tg = -32°C) NVP: N-vinyl-2-pyrrolidone (glass transition temperature of its homopolymer: Tg = approx. 80°C) AOMA (registered trademark): Cyclopolymerizable monomer manufactured by Nippon Shokubai Co., Ltd. (in the general formula (1), R 1 is a methyl group, R 2is a hydrogen atom.) (The glass transition temperature of the homopolymer is about 80°C.) V#216: acrylic acid-2-butylcarbamoyloxyethyl ester (Viscoat #216, manufactured by Osaka Organic Chemical Industry Co., Ltd.) (in the general formula (2), R 3 -CH2CH2-, R 4 is n-butyl group, R 5 is a hydrogen atom.) (The glass transition temperature of the homopolymer is Tg = 0°C) MMA: Methyl methacrylate HEA: Hydroxyethyl acrylate AIBN: 2,2'-azobisisobutyronitrile Irgacure 184: Photopolymerization initiator (manufactured by BASF) Irgacure 651: Photopolymerization initiator (manufactured by BASF) DCPMA: dicyclopentanyl methacrylate CHMA: Cyclohexyl methacrylate AA: Acrylic acid C / HX: Coronate HX (Tosoh Corporation, isocyanate-based crosslinking agent) D110N: Takenate D110N (manufactured by Mitsui Chemicals, isocyanate-based crosslinking agent) HDDA: 1,6-Hexanediol diacrylate BPO: Peroxide (Niper BMT-40SV, manufactured by Nippon Oil & Fats Co., Ltd.) Nasem ferric: Iron catalyst (manufactured by Nippon Chemical Industries Co., Ltd.) Irganox 1010: Antioxidant (manufactured by BASF) KBM403: Silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0175] <Adhesive strength to polyimide film> After peeling off the separator with the small peeling strength (MRQ50T100J) from the adhesive film, a 25μm thick polyimide substrate (product name "Upilex 25RN", manufactured by Ube Industries) was attached to produce an adhesive film with a polyimide substrate. The adhesive film with the polyimide substrate was cut to a width of 25mm and a length of 100mm, and the separator (JT-50Wa) was peeled off to expose the adhesive. This was then attached to a polyimide film (product name "Upilex 50S", manufactured by Ube Industries) using a 2kg hand roller back and forth once to obtain an evaluation sample. The obtained evaluation sample was stored at room temperature for 30 minutes, and then measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. After setting the evaluation sample on the tensile tester, the tensile test was started. The conditions of the tensile test were peel angle: 180 degrees, peel speed (pulling speed): 300 mm / min. The load when peeling the adhesive film from the polyimide film (Upilex 50S) was measured, and the average load at that time was taken as the adhesive strength.

[0176] <Adhesion to glass> The adhesive film with the polyimide substrate was cut to a width of 25 mm x length of 100 mm, the separator (JT-50Wa) was peeled off to expose the adhesive, and instead of adhering it to a polyimide film (product name "Upilex 50S", manufactured by Ube Industries) with one back and forth motion of a 2 kg hand roller, the adhesive film with the polyimide substrate was cut to a width of 25 mm x length of 100 mm, the separator (JT-50Wa) was peeled off to expose the adhesive, and the film was adhered to the non-tin side of glass (product name: S2004U8, manufactured by Matsunami Glass Industry Co., Ltd.) with one back and forth motion of a 2 kg hand roller, but the same measurement method as above for <Adhesive strength to polyimide film> was used.

[0177] <Storage modulus G'> The storage modulus G' corresponds to the portion stored as elastic energy when a material is deformed, and is an index indicating the degree of hardness. Only the adhesive layer was taken out from the adhesive film, laminated to a thickness of about 1 mm, and this was punched out to a diameter of 9 mm to prepare a cylindrical pellet, which was used as a measurement sample. Using a dynamic viscoelasticity measuring device (Rheometrics, ARES), the obtained measurement sample was fixed to a jig of φ8 mm parallel plates, and the storage modulus G' was calculated. The measurement conditions were as follows: Measurement: Shear mode Temperature range: -60℃~210℃ Heating rate: 5℃ / min Frequency: 1Hz

[0178] <Weight average molecular weight Mw> The weight average molecular weight was measured by gel permeation chromatography (GPC). Specifically, an Agilent 1260 Infinity (Agilent Technologies) was used as a GPC measuring device, and a 0.1% by weight amine-based component-added tetrahydrofuran solution was prepared in consideration of the polymer concentration of the sample, left for 20 hours, filtered through a 0.45 μm membrane filter, and the filtrate was subjected to GPC measurement. Measurements were performed under the following conditions, and values ​​were calculated in terms of standard polystyrene. (Molecular weight measurement conditions) Sample concentration: 0.1% by weight (amine-based component added tetrahydrofuran solution) Sample injection volume: 100μL Column: Product name "TSKgel GMH-H(S)" (manufactured by Tosoh Corporation) Eluent: Tetrahydrofuran with added amine components ·Flow rate: 0.5mL / min Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40℃ Standard sample: Polystyrene (PS)

[0179] [Production Example 1]: Production of acrylic polymer (1) In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 2EHA: 68.0 parts by weight, LA: 19.4 parts by weight, BA: 7.8 parts by weight, 4HBA: 3.9 parts by weight, AOMA (registered trademark): 1.0 parts by weight, and AIBN: 0.1 parts by weight as a polymerization initiator were added, and ethyl acetate was added so that the total concentration of these was 42% by weight. The system was replaced with nitrogen over 1 hour while gently stirring, and the liquid temperature in the flask was kept at around 58 ° C. to carry out a polymerization reaction for 5 hours. After the reaction was completed, ethyl acetate was added to adjust the polymer concentration to 32% by weight, and a solution of acrylic polymer (1) was obtained. The results are shown in Table 1.

[0180] [Production Examples 2 to 6, 8]: Production of acrylic polymers (2) to (6) and (8) Solutions of acrylic polymers (2) to (6) and (8) were obtained in the same manner as in Production Example 1, except that the monomer components and various conditions were changed as shown in Table 1. The results are shown in Table 1.

[0181] [Production Example 7]: Preparation of acrylic polymer (7) An acrylic resin (manufactured by Soken Chemical Industries, Ltd., product name "SK2137") obtained from 99.0 parts by weight of BA and 1.0 part by weight of 4HBA as monomer components was used as an acrylic polymer (7). The results are shown in Table 1.

[0182] [Production Example 9]: Production of acrylic oligomer (A) As monomer components, 60 parts by weight of DCPMA and 40 parts by weight of MMA, as a chain transfer agent, 3.5 parts by weight of α-thioglycerol, and as a polymerization solvent, 100 parts by weight of toluene were mixed and stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by weight of AIBN was added as a thermal polymerization initiator, and the mixture was reacted at 70°C for 2 hours, and then heated to 80°C and reacted for 2 hours to obtain an acrylic oligomer (A). The weight average molecular weight Mw of the acrylic oligomer (A) was 5100, and the glass transition temperature (Tg) was 130°C.

[0183] [Production Example 10]: Production of acrylic oligomer (B) As monomer components, CHMA: 95 parts by weight and AA: 5 parts by weight, α-methylstyrene dimer (manufactured by NOF Corporation, trade name "NOFMA-MSD"): 10 parts by weight as a chain transfer agent, AIBN: 10 parts by weight as a thermal polymerization initiator, and toluene were mixed so that the raw material concentration was 50% by weight, and reacted at 85°C for 2 hours under a nitrogen atmosphere. Next, the temperature was raised to 86°C and reacted for 1.5 hours to obtain an acrylic oligomer (B). The weight average molecular weight of the acrylic oligomer (B) was 4000, and the glass transition temperature (Tg) was 67°C.

[0184] Example 1 Acrylic polymer (1): 100 parts by weight, C / HX: 0.09 parts by weight as a crosslinking agent, acrylic oligomer (A): 2 parts by weight, Irganox 1010: 0.3 parts by weight as an antioxidant, and ferric nasem: 0.01 parts by weight as a catalyst were mixed, thoroughly stirred, and diluted with ethyl acetate and acetylacetone of 2% by weight of the solvent so that the total solid content was 21% by weight, to obtain a coating solution of acrylic adhesive composition (1). The obtained coating solution of acrylic adhesive composition (1) was applied to the silicone-treated surface of a release sheet (product name: JT-50Wa, manufactured by Nitto Denko Corporation) made of polyester resin with a thickness of 50 μm and silicone-treated on one side, so that the thickness after drying was 13 μm, and dried under the conditions of a drying temperature of 130 ° C. and a drying time of 1 minute. Next, a release sheet (product name: MRQ50T100J, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with a thickness of 50 μm and one side of which was silicone-treated was attached to the surface of the obtained adhesive layer so that the silicone-treated surface was in contact with the surface, thereby obtaining an adhesive film (1). This was aged at 50° C. for 3 days and various evaluations were performed. The results are shown in Table 3.

[0185] [Examples 2 to 9] Except for changing the raw material composition and various conditions as shown in Table 2, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic pressure-sensitive adhesive compositions (2) to (9) and pressure-sensitive adhesive films (2) to (9). These were aged at 50°C for 3 days and various evaluations were carried out. The results are shown in Table 3.

[0186] [Comparative Examples 1 to 5] Except for changing the raw material composition and various conditions as shown in Table 2, the same procedure as in Example 1 was carried out to obtain coating solutions of acrylic pressure-sensitive adhesive compositions (C1) to (C5) and pressure-sensitive adhesive films (C1) to (C5). These were aged at 50°C for 3 days and various evaluations were carried out. The results are shown in Table 3.

[0187] [Table 1]

[0188] [Table 2]

[0189] [Table 3] [Industrial Applicability]

[0190] The acrylic pressure-sensitive adhesive sheet and the like according to the embodiments of the present invention can be used for so-called flexible devices such as foldable devices and rollable devices. [Explanation of symbols]

[0191] 1000 Foldable Devices 100 Adhesive Film 10 Cover film 20 Adhesive layer 30 Polarizing plate 40 Adhesive layer 50 Touch Sensor 60 Adhesive layer 70 OLED 80 Adhesive layer 90 Base material layer

Claims

1. At 23°C, at a peel speed of 300 mm / min and a peel angle of 180°, the adhesive strength to polyimide film is 5.5 N / 25 mm or more, and the adhesive strength to glass is 5.5 N / 25 mm or more; The storage modulus G' at -20°C measured at a frequency of 1 Hz is 200 kPa or less, The thickness is 1 μm to 23 μm, It is formed from an acrylic pressure-sensitive adhesive composition, The acrylic pressure-sensitive adhesive composition contains an acrylic polymer (P) having a weight average molecular weight Mw of 500,000 to 2,500,000, a crosslinking agent, and an acrylic oligomer, the content of the acrylic polymer (P) in the acrylic pressure-sensitive adhesive composition is 50% by weight or more, the content of the crosslinking agent in the acrylic pressure-sensitive adhesive composition is 0.01 to 1 part by weight based on 100 parts by weight of the acrylic polymer (P); the content ratio of the acrylic oligomer in the acrylic pressure-sensitive adhesive composition is 0.1 parts by weight to 6.5 parts by weight based on 100 parts by weight of the acrylic polymer (P); The acrylic polymer (P) is obtained by polymerizing a monomer component (M), the monomer component (M) comprises at least one selected from the group consisting of a monomer (1) represented by general formula (1), a monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone; 【Chemistry 1】 (In general formula (1), R 1 is an alkyl group having 1 to 3 carbon atoms, R 2 is a hydrogen atom.) 【Chemistry 2】 (In general formula (2), R 3 is an alkylene group having 1 to 3 carbon atoms, R 4 is an alkyl group having 2 to 6 carbon atoms; R 5 is a hydrogen atom.) the content of at least one monomer selected from the group consisting of monomer (1) represented by general formula (1), monomer (2) represented by general formula (2), and N-vinyl-2-pyrrolidone in the monomer component (M) is 0.01% by weight to 10% by weight; The monomer component (M) contains an alkyl (meth)acrylate, The content of alkyl (meth)acrylate in the monomer component (M) is 50% by weight to 99% by weight, the alkyl(meth)acrylate comprises an alkyl(meth)acrylate (m1) having a homopolymer glass transition temperature Tg in the range of −80° C. to −60° C., and an alkyl(meth)acrylate (m2) having a homopolymer glass transition temperature Tg in the range of −40° C. to −10° C., The content of the alkyl (meth)acrylate (m1) in the monomer component (M) is 40% by weight to 80% by weight, The content of the alkyl (meth)acrylate (m2) in the monomer component (M) is 5% by weight to 50% by weight, The monomer component (M) contains a hydroxyl group-containing monomer (m4), the content ratio of the hydroxyl group-containing monomer (m4) in the monomer component (M) is 0.5% by weight to 15% by weight; Acrylic adhesive sheet.

2. 2. The acrylic pressure-sensitive adhesive sheet according to claim 1, wherein the acrylic oligomer has a weight average molecular weight Mw of 1,000 to 30,000.

3. A pressure-sensitive adhesive film having a pressure-sensitive adhesive layer constituted by the acrylic pressure-sensitive adhesive sheet according to claim 1 or 2.

4. A flexible device comprising the adhesive film according to claim 3.

Citation Information

Patent Citations

  • Optical recording and reproducing unit

    JP1981000039A

  • Alkailine zinc storage battery

    JP1988076271A

  • Adhesive sheet, laminate, and device

    JP2018168305A

  • Adhesive sheet, optical film with adhesive layer, multilayer body and image display device

    JP2020122140A

  • Adhesive sheet, repeated bending laminate member and repeated bending device

    JP2020139035A